The last Mayans: a reflection on ethnography and photography - Medina Hernández, Andrés (2021)
The discovery of the Bonampak wall paintings in the Lacandon Jungle, in the 40s of the last century, caused great commotion in the anthropological, artistic and governmental sectors, as it brought up several disturbing questions, both about this ancient Mesoamerican civilization and in relation with the Lacandon population living around it. Astonishment, curiosity and the eagerness to clarify numerous questions raised are condensed, in some way, in the photographic work of Gertrude Duby, which we refer to as a perspective that combines the photographic technique with an ethnographic look typical of her time.